2021
DOI: 10.1186/s12872-021-02000-x
|View full text |Cite
|
Sign up to set email alerts
|

The association between homocysteine levels and cardiovascular disease risk among middle-aged and elderly adults in Taiwan

Abstract: Background Our study aimed to determine the association between homocysteine levels and cardiovascular disease (CVD) risk in middle-aged and elderly adults in a community in northern Taiwan. Methods Participants in our study included adults aged 50 to 85 years old during community health examinations in 2019. A total of 396 people were enrolled, the ethnicity of all participants is Chinese. We divided participants according to tertiles of ln[homocy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…Conventional risk factors of CVDs such as dyslipidemia, hypertension, smoking, or diabetes mellitus do not fully clarify all CVD events and deaths. Several studies summarized that elevated plasma Hcy denotes an independent risk factor for CVDs other than conventional risk factors and can be applied as a biomarker to predict CVD onset in individuals [77][78][79].…”
Section: Cvds Are Associated With Elevated Plasma Hcymentioning
confidence: 99%
“…Conventional risk factors of CVDs such as dyslipidemia, hypertension, smoking, or diabetes mellitus do not fully clarify all CVD events and deaths. Several studies summarized that elevated plasma Hcy denotes an independent risk factor for CVDs other than conventional risk factors and can be applied as a biomarker to predict CVD onset in individuals [77][78][79].…”
Section: Cvds Are Associated With Elevated Plasma Hcymentioning
confidence: 99%
“…Homocysteine (Hcy) is a sulfhydryl amino acid situated at a branch point of methionine metabolism that is metabolized via two interrelated processes of remethylation and transsulfuration [ 1 ]. Numerous studies have found that elevated serum Hcy is a nontraditional independent risk factor for cardiovascular disease (CVD) [ 2 , 3 ]. Elevated serum Hcy is a common finding in patients with chronic kidney disease (CKD) [ 4 ], which is attributed to reduced renal clearance of circulating Hcy and impaired Hcy metabolism [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, dynamic alterations in the gene expression landscape can contribute to the progression of CVDs (10). The dynamic gene expression landscape is subject to different levels of regulation, including genetics, epitranscriptomics, transcriptomics, and epigenetics (11). Epigenetics provides the link between genetic programming and environmental influence that results in the expressed phenotype (12).…”
Section: Introductionmentioning
confidence: 99%